1st Inter-Continental Concert: The Reunion of the Legends - Mosallaeipour, Sam; Mohseni Zonoozi, Shahed (http://intercontinentalconcerts.org, 2012)
[Abstract Not Available]
Keywords: Intercontinental Concerts; The reunion of the legends; Sam Mosallaeipour; Shahed Mohseni Zonoozi; Musical Record, Concert Video